Apoyo en la supervisión técnica de proyectos de la Secretaria de Planeación e Infraestructura en el municipio de Belén, Boyacá (2023)
In the following dissemination article, each of the activities carried out as an intern in the Planning and Infrastructure Secretariat of the municipality of Belén, in the department of Boyacá, is presented and described through a detailed report. The internship was carried out in support of the technical supervision of civil works projects that were being carried out. To achieve this purpose, the qualitative research methodology was used, describing in detail the activities, which included verification of the work carried out by the yellow machinery, supervision of contracts executed in administrative matters, supervision of compliance with technical and legal regulations. to guarantee the quality of civil works, calculation of work quantities and comparison with Unit Price Analysis of the Government of Boyacá and preparation of reports on technical visits to the various projects that were executed in the municipality and that benefit the population. With the completion of this professional practice, the concepts, theories and knowledge learned in the classroom are implemented, to be demonstrated through skills, abilities and human values reflected in the daily life of work, guaranteeing the correct execution of tasks. assigned and the efficiency, effectiveness and quality of the results. Likewise, by doing an internship in a public entity, it gives the student an advantage in experience and expertise to face professional challenges, better understand the nation's public system, and perform assertively in any other work environment, in their professional field. of the abstract into English or Portuguese, the third person narrative grammatical structure must be preserved.